Vortioxetine as an alternative treatment for somatic symptom disorder: case report - Furutani, Naoki; Nagoshi, Yasuhide (Frontiers in Psychiatry, 2024)
Somatic symptom disorder (SSD) is characterized by persistent physical symptoms that cause significant distress and functional impairment. Despite the widespread use of serotonin reuptake inhibitors (SRIs) in treating SSD, some patients experience insufficient response, necessitating alternative therapeutic approaches. We report two cases of SSD that demonstrated significant improvement with vortioxetine, a novel antidepressant with multimodal serotonergic receptor activity. In Case 1, an 88-year-old female with throat discomfort and cough experienced an insufficient response to an SRI. After switching to vortioxetine, she achieved significant symptom relief within 10 days, with no relapse observed over the following four months. In Case 2, a 29-year-old female presenting with widespread somatic pain and palpitations, unresponsive to analgesics, achieved symptom resolution within two weeks with the initial use of vortioxetine. The therapeutic effects of vortioxetine were rapid and well-tolerated. These cases highlight the potential of vortioxetine for treating SSD, particularly in cases of insufficient response to SRIs, and suggest a possible overlap between SSD and obsessive-compulsive spectrum disorders through its action on serotonergic pathways.